Industrial Unified Recuperative Heat Exchanger on the Basis of «Silal» M-I 115x460x860-05 and «Silal» M-II 230x460x860-1,0 (standard series M-I and M-II) Module Elements - A. P. Nesenchuk; N. L. Mandel; V. N. Shishkov; G. S. Novgorodova; T. V. Ryzhova; M. G. Pshonik (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes a fundamentally new modification of cast iron recuperative heat exchanger assembled on the basis of the following modules: «Silal» M-I 115x460x860-05 and «Silal» M-II 230x460x860-1.0.It is shown that such recuperative heat exchanger does not have the disadvantages which are inherent to presently applied recuperators.